2020
DOI: 10.1002/jcsm.12578
|View full text |Cite
|
Sign up to set email alerts
|

A subset of microRNAs in the Dlk1‐Dio3 cluster regulates age‐associated muscle atrophy by targeting Atrogin‐1

Abstract: Background The microRNAs (miRNAs) down-regulated in aged mouse skeletal muscle were mainly clustered within the delta-like homologue 1 and the type III iodothyronine deiodinase (Dlk1-Dio3) genomic region. Although clustered miRNAs are coexpressed and regulate multiple targets in a specific signalling pathway, the function of miRNAs in the Dlk1-Dio3 cluster in muscle aging is largely unknown. We aimed to ascertain whether these miRNAs play a common role to regulate age-related muscle atrophy. Methods To examine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 73 publications
1
14
0
Order By: Relevance
“…Indeed, the phenotype of regenerating shMeg3-treated muscle conspicuously resembles age-related muscle defects (Beggs et al 2004;Lukjanenko et al 2019). Recently, a subset of Dlk1-Dio3 miRNAs have been shown to suppress age-related atrophy (Shin et al 2020), and these ncRNAs -including Meg3 -are markedly downregulated in aged muscle (Mikovic et al 2018). Given that aged satellite cells accumulate epigenetic abnormalities that suppress their ability to efficiently regenerate muscle (Liu et al 2013;Sousa-Victor et al, 2014), we postulate that age-related Meg3 downregulation in muscle induces a reprogramming of the epigenetic landscape that is more sensitized to pathological TGFβ and EMT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the phenotype of regenerating shMeg3-treated muscle conspicuously resembles age-related muscle defects (Beggs et al 2004;Lukjanenko et al 2019). Recently, a subset of Dlk1-Dio3 miRNAs have been shown to suppress age-related atrophy (Shin et al 2020), and these ncRNAs -including Meg3 -are markedly downregulated in aged muscle (Mikovic et al 2018). Given that aged satellite cells accumulate epigenetic abnormalities that suppress their ability to efficiently regenerate muscle (Liu et al 2013;Sousa-Victor et al, 2014), we postulate that age-related Meg3 downregulation in muscle induces a reprogramming of the epigenetic landscape that is more sensitized to pathological TGFβ and EMT signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of miR-23a was sufficient to protect the muscle from atrophy both in vitro and in vivo (Wada et al, 2011 ). Direct interactions were identified between miR-376c-3p and the 3′ UTR of Atrogin-1, leading to repression of Atrogin-1, and thereby induction of eIF3f protein levels in both human and mouse skeletal muscle cells (Shin et al, 2020 ). Reportedly, lncRNA Pvt1 is upregulated during muscle atrophy by blocking c-Myc phosphorylation and degradation.…”
Section: Ncrnas In Muscle Diseasementioning
confidence: 99%
“…The 5 miRNAs (miR-377, miR-495, miR-1197, miR-379, and miR-376c) that were downregulated in aged mice were also negatively correlated with age in the gluteus maximus muscles from humans. 75 When the primary miRNA (pri-miRNA) and mature miRNA expression levels were compared among six elderly (70 ± 2 years) and six younger (29 ± 2 years) men in a study of skeletal muscle biopsies, it was found that pri-miRNA-1-1, pri-miRNA-1-2, pri-miRNA-133a-1, and pri-miRNA-133a-2 were upregulated in the elderly; however, mature miRNA-1 and miRNA-133a were not disturbed. 76 , 77 …”
Section: Ncrnas In Muscle Atrophy Induced By Agingmentioning
confidence: 99%